Investigation of Emissivity and Junction Contacting Status of C-Type Thermocouples Using Rich Hencken Flames - Linqing Zhang; Yingrong Lu; Qinghuang Huang; Peiyong Wang; Juntao Chang (Energies)
C-type thermocouples are widely used to measure rich combustions; however, the measured temperature, i.e., the thermocouple junction temperature, is not equal to the gas temperature. The junction temperature results from the junction energy balance, including radiation with environments, conduction with thermocouple wires, and convection with gas. A correction based on the junction energy conservation can derive the gas temperature from the measured temperature. Two C-type thermocouples are used to measure the core region of the standard flames with known gas velocity, composition, and temperature. By matching the CFD-simulated junction temperature with the measured temperature, the emissivity of the thermocouples is obtained. In the temperature range of 1190–1542 K, the emissivity of both thermocouples is close to 0.4. Since the junctions of the C-type thermocouple are large, the area ratios of the wire cross-section to the junction surface are small, and the wire conduction effect is minimal. CFD simulations show that the junction temperatures only decrease by 3.9 K and 8.1 K without wire conduction when the 0.5 mm and 1.0 mm thermocouples measure the Hencken flame with the temperature of 2023.5 K. With the CFD simulation of the measurement of the diffusion region of the Hencken flame, where a strong gas temperature gradient exists, the junction contacting status is judged for the 0.5 mm thermocouple. The simulated temperature of the welding point is consistent with the measured temperature, indicating no wire contact inside the junction.